Readiness of Islamic Human Resources In Supporting The Development of Halal Tourism In West Jawa (Evidence From Hospitality Industry) - Joeliaty, Joeliaty; Noni Evita, Siti; Ode Zunita, Wa (Cv. Syntax Corporation Indonesia, 2021)
Introduction : The development of halal tourism experienced the largest growth compared to other types of tourism until 2018 in Indonesia. These developments lead to an increasingly higher level of human resources with skills and competencies in the field of sharia-compliant tourism services. Objective : This research will explain the readiness of Islamic human resources to deal with such changes. The study examined the issue of Islamic HUMAN RESOURCES in Sharia Hotels with a sample of 200 employees as respondents. Method : This research uses a qualitative approach, namely rasch model and SWOT analysis so that measurements with likert scale are more precise. Since the study's problems have never been studied before and there are not enough variables and constructions available, the authors use an exploratory approach. Results : The results of this study show that the readiness of Shariah human resources in Sharia Hotels as measured by various competencies shows mixed results. Intellectual competence and competence in sharia science are found from low categories. In addition, anxiety levels and fatigue levels are high. Conclusion : The readiness of human resources in Shariah hotels shows mixed results. The opportunity for islamic human resources management lies in the implementation of halal tourism standardization, both national and international standards. However, hospitality also faces a threat, namely an increase in the number of competitors. Therefore, the national halal hotel hospitality industry requires adequate education and training in Islamic human resources, both by relevant government agencies and other stakeholders. This effort is to support the increase of national halal tourism, especially in sharia hotel areas in West Java.